De novo assembly and analysis of the transcriptome of the Siberian wood frog Rana amurensis - D. N. Smirnov; S. V. Shekhovtsov; A. A. Shipova; G. R. Gazizova; E. I. Shagimardanova; N. A. Bulakhova; E. N. Meshcheryakova; T. V. Poluboyarova; E. E. Khrameeva; S. E. Peltek; D. I. Berman (Вавиловский журнал генетики и селекции)
The Siberian wood frog Rana amurensis Boulenger, 1886 is the most hypoxia-tolerant amphibian. It can survive for several months in an almost complete absence of oxygen. Little is known about the mechanisms of this remarkable resilience, in part because studies of amphibian genomes are impeded by their large size. To make the Siberian wood frog more amenable for genetic analysis, we performed transcriptome sequencing and de novo assembly for the R. amurensis brain under hypoxia and normoxia, as well as for the normoxic heart. In order to build a de novo transcriptome assembly of R. amurensis, we utilized 125-bp paired-end reads obtained from the brain under normoxia and hypoxia conditions, and from the heart under normoxia. In the transcriptome assembled from about 100,000,000 reads, 81.5 % of transcripts were annotated as complete, 5.3 % as fragmented, and 13.2 % as missing. We detected 59,078 known transcripts that clustered into 22,251 genes; 11,482 of them were assigned to specific GO categories. Among them, we found 6696 genes involved in protein binding, 3531 genes involved in catalytic activity, and 576 genes associated with transporter activity. A search for genes encoding receptors of the most important neurotransmitters, which may participate in the response to hypoxia, resulted in a set of expressed receptors of dopamine, serotonin, GABA, glutamate, acetylcholine, and norepinephrine. Unexpectedly, no transcripts for histamine receptors were found. The data obtained in this study create a valuable resource for studying the mechanisms of hypoxia tolerance in the Siberian wood frog, as well as for amphibian studies in general.